2020
DOI: 10.1016/j.heliyon.2020.e03882
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of red LED irradiation on fibroblasts and co-culture of adipose-derived mesenchymal stem cells

Abstract: The objective of this study was to evaluate the effects of red Light Emiting Diode (red LED) irradiation on fibroblasts in adipose-derived mesenchymal stem cells (ASC) co-culture on the scratch assay. We hypothesized that red LED irradiation could stimulate paracrine secretion of ASC, contributing to the activation of genes and molecules involved in cell migration and tissue repair. ASC were co-cultured with NIH/3T3 fibroblasts through direct contact and subjected to red LED irradiation (1.45 J/cm 2 /5min6s) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…These results may imply that our LED treatment stimulated angiogenesis by activating other growth factors, rather than VEGF. A previous in vitro study reported that red LED irradiation exhibits an inhibitory effect on VEGF expression, which correlates with our findings 24 . In addition, an in vivo study using BALB/c mice implanted with HeLa cells also demonstrated that red LED light attenuated VEGF expression 25 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results may imply that our LED treatment stimulated angiogenesis by activating other growth factors, rather than VEGF. A previous in vitro study reported that red LED irradiation exhibits an inhibitory effect on VEGF expression, which correlates with our findings 24 . In addition, an in vivo study using BALB/c mice implanted with HeLa cells also demonstrated that red LED light attenuated VEGF expression 25 .…”
Section: Discussionsupporting
confidence: 91%
“…A previous in vitro study reported that red LED irradiation exhibits an inhibitory effect on VEGF expression, which correlates with our findings. 24 In addition, an in vivo study using BALB/c mice implanted with HeLa cells also demonstrated that red LED light attenuated VEGF expression. 25 Indeed, many studies have indicated that FGF is the primary growth factor stimulated by red LED irradiation.…”
Section: Discussionmentioning
confidence: 98%
“…Since no data was found on combined treatment with locoregional and immunotherapy in the setting of transplantation, data outside transplant setting was assessed. In this context, a total of 450 references were identified, whereas 14 were eventually included for further review (Supplementary Table S10) [105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Two of these were systematic reviews and meta-analyses [105,106].…”
Section: Strength Of Recommendation: N/amentioning
confidence: 99%